Teaching STEM in the early years : activities for integrating science, technology, engineering, and mathematics - Moomaw, Sally, 1948- (Redleaf Press, 2013)
"The foundation for science, technology, engineering, and mathematics education begins in the early years. Teaching STEM in the Early Years provides activities and learning center ideas that seamlessly integrate STEM throughout your early childhood classroom"--Resumé vydavatele
Terminologický slovník
Keywords: přírodovědné vzdělávání; předškolní výchova; science education; preschool education; metodické příručky; methodological manuals